2014
DOI: 10.1111/jvim.12407
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin I and T as Prognostic Markers in Cats with Hypertrophic Cardiomyopathy

Abstract: BackgroundMyocardial injury detected by cardiac troponin I and T (cTnI and cTnT) in cardiac disease is associated with increased risk of death in humans and dogs.HypothesisPresence of myocardial injury predicts long‐term death in cats with hypertrophic cardiomyopathy (HCM), and ongoing myocardial injury reflects change in left ventricular wall thickness over time.AnimalsThirty‐six cats with primary HCM.MethodsProspective cohort study. Cats with HCM were included consecutively and examined every 6 months. Echoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
72
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 35 publications
6
72
2
3
Order By: Relevance
“…Whereas a previous study did not find a significant difference; in our study, a significant difference was found between the cTnI concentration of cats with compensated severe HCM and those with compensated disease under treatment. This finding could implicate ongoing damage of the myocardium with disease progression despite clinical stabilization under treatment and supports the findings of another study, in which cTnI concentration at admission was prognostic for survival. In humans with stable chronic heart failure, 1 study found that higher baseline cTnI concentration and an increase over a 6‐month period were independent significant prognostic predictors of adverse outcome.…”
Section: Discussionsupporting
confidence: 92%
“…Whereas a previous study did not find a significant difference; in our study, a significant difference was found between the cTnI concentration of cats with compensated severe HCM and those with compensated disease under treatment. This finding could implicate ongoing damage of the myocardium with disease progression despite clinical stabilization under treatment and supports the findings of another study, in which cTnI concentration at admission was prognostic for survival. In humans with stable chronic heart failure, 1 study found that higher baseline cTnI concentration and an increase over a 6‐month period were independent significant prognostic predictors of adverse outcome.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, the detection limit of the current cTnI assay is 0.006 ng/mL. A previous study reported that the mean serum cTnI concentration in 23 pure‐bred healthy cats was 0.012 (range, 0.003‐0.09) ng/mL . In our study, the median concentration was 0.027 (IQR, 0.012‐0.048) ng/mL in healthy cats.…”
Section: Discussioncontrasting
confidence: 74%
“…Previously reported variables that have been shown to have an association with survival time in cats with CHF or HCM include body weight, age, body temperature at the time of hospital admission, left atrial size and function, extreme left ventricular hypertrophy, left ventricular systolic function, presence of systolic anterior motion, and cardiac troponin I 35, 36, 37, 44, 45, 46. Although troponin I was not measured, none of the other variables were found to be associated with survival time in the current study, which may be due to the small sample size or to a true lack of association in this population of cats.…”
Section: Discussionmentioning
confidence: 99%